2004
DOI: 10.1093/carcin/bgh327
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the MMP1 and MMP3 promoter and non-small cell lung carcinoma in North China

Abstract: Matrix metalloproteinases (MMPs) are proteolytic enzymes that regulate various cell behaviors in cancer biology, via their basic function of degradation of proteins. Genetic variations in several MMP promoters may influence transcription and expression of MMPs. The aim of this study is to assess the effects of the two single nucleotide polymorphisms (SNPs), the guanine insertion polymorphism in the MMP1 promoter and the adenosine insertion polymorphism in the MMP3 promoter, on risk of the development and lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
96
3
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 27 publications
13
96
3
2
Order By: Relevance
“…The MMP 2G/6a haplotype was associated with lower risk of lymphatic metastasis of lung cancer when compared to the 1G/5a haplotype in a chinese population (69). However, in a uS population, another haplotype (1G/6a/82a/1082G), including MMP-1 (1G/2G), MMP-3 (5a/6a) and MMP-12 (-82aG, 1082a/G), showed an association with a higher risk of lung cancer among never smokers (14).…”
Section: Haplotype Influencementioning
confidence: 88%
See 1 more Smart Citation
“…The MMP 2G/6a haplotype was associated with lower risk of lymphatic metastasis of lung cancer when compared to the 1G/5a haplotype in a chinese population (69). However, in a uS population, another haplotype (1G/6a/82a/1082G), including MMP-1 (1G/2G), MMP-3 (5a/6a) and MMP-12 (-82aG, 1082a/G), showed an association with a higher risk of lung cancer among never smokers (14).…”
Section: Haplotype Influencementioning
confidence: 88%
“…Fang et al (69) showed that the 1G/6a haplotype may play a protective role in the development of adult astrocytoma, whereas the MMP-3 5a/6a polymorphism is not necessarily an independent factor influencing susceptibility to astrocytoma in individuals from northern china.…”
Section: Haplotype Influencementioning
confidence: 99%
“…Two studiers were further excluded for not on the association between MMP1 rs1799750 polymorphism and lung cancer risk (Zhou et al, 2005;Sauter et al, 2008). Thus, 9 case-control studies with a total of 4823 cases and 4298 controls finally met the inclusion criteria and were included in the meta-analysis (Zhu et al, 2001;Fang et al, 2005;Su et al, 2006;Zhang et al, 2006; Cheng, 2007;Wei et al, 2007;Gonzalez-Arriaga et al, 2008;Hart et al, 2011;. The distribution of genotypes for MMP1 rs1799750 polymorphism in the controls of all studies was consistent with that expected from the HWE.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of those 9 studies, sample sizes ranged from 146 to 3337, in which four studies focused on nonsmall cell lung cancer (NSCLC) and five ones on mixed lung cancers. There were four studies on Caucasians (Zhu et al, 2001;Su et al, 2006;Gonzalez-Arriaga et al, 2008;Hart et al, 2011), and five studies on Asians (Fang et al, 2005;Zhang et al, 2006;Cheng, 2007;Wei et al, 2007;. Almost all of the cases were histologically confirmed, while controls were mainly matched for sex and age.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The selected SNPs were also previously analyzed in other cancers, such as lung, stomach, ovarian and bladder cancer. The results of these studies point to a positive correlation between MMPs polymorphism and the susceptibility to develop cancer, tumor invasiveness and further progression of the disease [22,23].…”
mentioning
confidence: 97%